Transcription initiation by RNA polymerase II is inhibited by S-adenosylhomocysteine. - Jove, R (1982)
Most eukaryotic mRNAs are blocked at their 5' termini by guanylylation and methylation. These "cap structures" have been shown to play important roles in increasing the stability and translatability of mRNAs. Previous in vitro and in vivo data suggest that these modifications occur extremely early in the synthesis of RNA transcripts by RNA polymerase II. Here we show that S-adenosylhomocysteine (AdoHcy), both a product and an inhibitor of transmethylation reactions, inhibits transcription initiation by RNA polymerase II, but not by RNA polymerase III, in a HeLa whole-cell lysate. AdoHcy must be present during initiation to inhibit transcription and does not affect elongation by RNA polymerase II or the stability of the resultant transcript. Furthermore, AdoHcy does not inhibit transcription by purified HeLa RNA polymerase II. These results suggest that formation of the 5'-cap structure is coupled to initiation of transcription and is consistent with a close association between the capping enzymes and RNA polymerase II at the time of initiation.